Fractional Itô–Doob Stochastic Differential Equations Driven by Countably Many Brownian Motions - Abdellatif Ben Makhlouf; Lassaad Mchiri; Hakeem A. Othman; Hafedh M. S. Rguigui (Fractal and Fractional, 2023)
This article is devoted to showing the existence and uniqueness (EU) of a solution with non-Lipschitz coefficients (NLC) of fractional Itô-Doob stochastic differential equations driven by countably many Brownian motions (FIDSDECBMs) of order <semantics>ϰ∈(0,1)</semantics> by using the Picard iteration technique (PIT) and the semimartingale local time (SLT).